O reisado boi coração: tesouro vivo no contexto da cultura e da educação na cidade de Ocara, Ceará - Xavier, Lisimére Cordeiro do Vale (2019)
The present thesis research has as a motivating or problematic cause generating the growing concern about the preservation, expansion and dissemination of Reisado Boi Coração as an integral and integrating part of the popular and educational cultural heritage of the municipality of Ocara, Ceará. This concern was and is a fundamental premise for the development of this research that is justified by professional personal interest, thematic feasibility and relevance. In this way, the following proposition was followed as a guideline: what is the value attributed to Reisado Boi Coração's devotion to identification and feeling of belonging to the local culture? Aiming to attend to the postulates of the problematic in allusion was listed as main objective: to understand and at the same time demonstrate the practice of Reisado Boi Coração as a local cultural and educational heritage. Therefore, the methodological procedures adopted for the construction of this research are those of the human and social sciences. As for the method, it approached the phenomenologicalhermeneutic of the empirical genre through field research. The objective is a descriptiveexploratory research. Regarding nature, research is classified as a strategic basic qualitative approach. Regarding the technical procedure, the ethnographic case study in the field of microculture prevails. The techniques used for data collection were: semi-structured interviews, participant observation, document analysis and oral history supplemented with images and the diary / field notes as a research tool. Data analysis techniques (information) were used to analyze the discourse. Concerning the theoretical reference, we have used, among others, authors such as: Abbagnano (2007); André (1995); Barroso (2008); Bauman (2013); Bogdan and Biklen (1994); Cascudo (1972, 2003); Cavalcanti (2000, 2006a, 2006b); Certeau (1998); Chartier (1990); Chizzotti (2011); Eliade (1992); Geertz (1973); Gil (2008); Gohn (1999, 2011); Hall (2003); Horta, Grunberg and Monteiro (2006); Laburthe-Tolra and Warnier (2010). It could be stated, a priori, that the culture of Reisado Boi Coração is vivid in the history and in the daily memory of the inhabitants of Ocara, who recognize it beyond material visuality. Reisado Boi Coração is included in the immaterial heritage of odd meanings for practitioners, participants and the general community of the municipality of Ocara.